'Ashley Wilkes Told Me He Likes to See a Girl with a Healthy Appetite': Food and drink in Margaret Mitchell's Gone with the Wind. Issue 2 (31st July 2012) - Tunc, Tanfer Emin
Despite the passage of three-quarters of a century since its publication in 1936, critics and biographers still grapple with how to place Margaret Mitchell's Gone with the Wind (GWTW) within southern literature. While some hail GWTW as an example of the 'Great American Novel', others see the work as contributing to the perpetuation of destructive stereotypes concerning African Americans, as well as a nostalgic distortion of life in the nineteenth-century South. Nevertheless, GWTW remains an important text because of the insight it provides into numerous aspects of southern culture, especially foodways. The novel is replete with direct and indirect references to the culinary culture of the South, and the ways in which this culture interacted with racial and gender constructions. The presence of food (from the Wilkes barbecue at Twelve Oaks, to Scarlett's and Rhett's honeymoon feasts in New Orleans) and its absence (especially during the Civil War) serve as an underexamined thread in the work which underscores the interface between black and white and male and female.